Analysis and optimum design of concrete reservoir wall - Brauns, Janis; Andersons, Guntis (Journal of Civil Engineering and Management, 2002)
The design problems of reservoirs for collection, safekeeping and utilization of aggressive sewage and liquid manure in agricultural production have been discussed. As economic construction of reservoirs are reinforced concrete cylindrical containers. The stress analysis and optimum design of the wall of open monolithic reservoir has been performed. The optimum parameters of reservoir wall are fixed taking into account strength and serviceability limit state requirements. Based on the results obtained, it is determined that economical solutions can be reached by using combinations of concrete and steel with high strength classes.Frist Published Online: 30 Jul 2012